fatmaramadhanisiagian@gmail.com - Br Siagian, Fatma Ramadhani (Nusantara: Journal of Cultural Research, 2025)
Technology plays an important role in economic development. The COVID-19 pandemic has changed people's lifestyles, encouraging businesses to shift to a digital approach. Although it has had a major impact on the economy, including MSMEs, the pandemic has also encouraged adaptation, innovation, and digital transformation through technology and artificial intelligence (AI). This study uses a qualitative descriptive method with data from articles, journals, books, and official publications. The objective is to explore the phenomenon of the Fourth Industrial Revolution in supporting SME growth through digital transformation and the utilization of AI. The research findings indicate that the 4th Industrial Revolution opens opportunities for SMEs to build sustainable businesses. SMEs are beginning to utilize digital technologies such as e-commerce, food delivery apps, and online business models. However, AI adoption remains limited, although some SMEs have already implemented chatbots for automated customer service. Government and private sector support is crucial to enable SMEs to adapt their business models to technological advancements, ensuring their survival and growth in the future.